(* Title: HOL/Algebra/RingHom.thy Author: Stephan Hohe, TU Muenchen *) theory RingHom imports Ideal begin section ‹Homomorphisms of Non-Commutative Rings› text ‹Lifting existing lemmas in a ‹ring_hom_ring› locale› locale ring_hom_ring = R?: ring R + S?: ring S for R (structure) and S (structure) + fixes h assumes homh: "h ∈ ring_hom R S" notes hom_mult [simp] = ring_hom_mult [OF homh] and hom_one [simp] = ring_hom_one [OF homh] sublocale ring_hom_cring ⊆ ring: ring_hom_ring by standard (rule homh) sublocale ring_hom_ring ⊆ abelian_group?: abelian_group_hom R S proof show "h ∈ hom (add_monoid R) (add_monoid S)" using homh by (simp add: hom_def ring_hom_def) qed lemma (in ring_hom_ring) is_ring_hom_ring: "ring_hom_ring R S h" by (rule ring_hom_ring_axioms) lemma ring_hom_ringI: fixes R (structure) and S (structure) assumes "ring R" "ring S" assumes hom_closed: "!!x. x ∈ carrier R ==> h x ∈ carrier S" and compatible_mult: "⋀x y. [| x ∈ carrier R; y ∈ carrier R |] ==> h (x ⊗ y) = h x ⊗⇘S⇙ h y" and compatible_add: "⋀x y. [| x ∈ carrier R; y ∈ carrier R |] ==> h (x ⊕ y) = h x ⊕⇘S⇙ h y" and compatible_one: "h 𝟭 = 𝟭⇘S⇙" shows "ring_hom_ring R S h" proof - interpret ring R by fact interpret ring S by fact show ?thesis proof show "h ∈ ring_hom R S" unfolding ring_hom_def by (auto simp: compatible_mult compatible_add compatible_one hom_closed) qed qed lemma ring_hom_ringI2: assumes "ring R" "ring S" assumes h: "h ∈ ring_hom R S" shows "ring_hom_ring R S h" proof - interpret R: ring R by fact interpret S: ring S by fact show ?thesis proof show "h ∈ ring_hom R S" using h . qed qed lemma ring_hom_ringI3: fixes R (structure) and S (structure) assumes "abelian_group_hom R S h" "ring R" "ring S" assumes compatible_mult: "⋀x y. [| x ∈ carrier R; y ∈ carrier R |] ==> h (x ⊗ y) = h x ⊗⇘S⇙ h y" and compatible_one: "h 𝟭 = 𝟭⇘S⇙" shows "ring_hom_ring R S h" proof - interpret abelian_group_hom R S h by fact interpret R: ring R by fact interpret S: ring S by fact show ?thesis proof show "h ∈ ring_hom R S" unfolding ring_hom_def by (auto simp: compatible_one compatible_mult) qed qed lemma ring_hom_cringI: assumes "ring_hom_ring R S h" "cring R" "cring S" shows "ring_hom_cring R S h" proof - interpret ring_hom_ring R S h by fact interpret R: cring R by fact interpret S: cring S by fact show ?thesis proof show "h ∈ ring_hom R S" by (simp add: homh) qed qed subsection ‹The Kernel of a Ring Homomorphism› ― ‹the kernel of a ring homomorphism is an ideal› lemma (in ring_hom_ring) kernel_is_ideal: "ideal (a_kernel R S h) R" apply (rule idealI [OF R.is_ring]) apply (rule additive_subgroup.a_subgroup[OF additive_subgroup_a_kernel]) apply (auto simp: a_kernel_def') done text ‹Elements of the kernel are mapped to zero› lemma (in abelian_group_hom) kernel_zero [simp]: "i ∈ a_kernel R S h ⟹ h i = 𝟬⇘S⇙" by (simp add: a_kernel_defs) subsection ‹Cosets› text ‹Cosets of the kernel correspond to the elements of the image of the homomorphism› lemma (in ring_hom_ring) rcos_imp_homeq: assumes acarr: "a ∈ carrier R" and xrcos: "x ∈ a_kernel R S h +> a" shows "h x = h a" proof - interpret ideal "a_kernel R S h" "R" by (rule kernel_is_ideal) from xrcos have "∃i ∈ a_kernel R S h. x = i ⊕ a" by (simp add: a_r_coset_defs) from this obtain i where iker: "i ∈ a_kernel R S h" and x: "x = i ⊕ a" by fast+ note carr = acarr iker[THEN a_Hcarr] from x have "h x = h (i ⊕ a)" by simp also from carr have "… = h i ⊕⇘S⇙ h a" by simp also from iker have "… = 𝟬⇘S⇙ ⊕⇘S⇙ h a" by simp also from carr have "… = h a" by simp finally show "h x = h a" . qed lemma (in ring_hom_ring) homeq_imp_rcos: assumes acarr: "a ∈ carrier R" and xcarr: "x ∈ carrier R" and hx: "h x = h a" shows "x ∈ a_kernel R S h +> a" proof - interpret ideal "a_kernel R S h" "R" by (rule kernel_is_ideal) note carr = acarr xcarr note hcarr = acarr[THEN hom_closed] xcarr[THEN hom_closed] from hx and hcarr have a: "h x ⊕⇘S⇙ ⊖⇘S⇙h a = 𝟬⇘S⇙" by algebra from carr have "h x ⊕⇘S⇙ ⊖⇘S⇙h a = h (x ⊕ ⊖a)" by simp from a and this have b: "h (x ⊕ ⊖a) = 𝟬⇘S⇙" by simp from carr have "x ⊕ ⊖a ∈ carrier R" by simp from this and b have "x ⊕ ⊖a ∈ a_kernel R S h" unfolding a_kernel_def' by fast from this and carr show "x ∈ a_kernel R S h +> a" by (simp add: a_rcos_module_rev) qed corollary (in ring_hom_ring) rcos_eq_homeq: assumes acarr: "a ∈ carrier R" shows "(a_kernel R S h) +> a = {x ∈ carrier R. h x = h a}" proof - interpret ideal "a_kernel R S h" "R" by (rule kernel_is_ideal) show ?thesis using assms by (auto simp: intro: homeq_imp_rcos rcos_imp_homeq a_elemrcos_carrier) qed lemma (in ring_hom_ring) hom_nat_pow: "x ∈ carrier R ⟹ h (x [^] (n :: nat)) = (h x) [^]⇘S⇙ n" by (induct n) (auto) lemma (in ring_hom_ring) inj_on_domain: ✐‹contributor ‹Paulo Emílio de Vilhena›› assumes "inj_on h (carrier R)" shows "domain S ⟹ domain R" proof - assume A: "domain S" show "domain R" proof have "h 𝟭 = 𝟭⇘S⇙ ∧ h 𝟬 = 𝟬⇘S⇙" by simp hence "h 𝟭 ≠ h 𝟬" using domain.one_not_zero[OF A] by simp thus "𝟭 ≠ 𝟬" using assms unfolding inj_on_def by fastforce next fix a b assume a: "a ∈ carrier R" and b: "b ∈ carrier R" have "h (a ⊗ b) = (h a) ⊗⇘S⇙ (h b)" by (simp add: a b) also have " ... = (h b) ⊗⇘S⇙ (h a)" using a b A cringE(1)[of S] by (simp add: cring.cring_simprules(14) domain_def) also have " ... = h (b ⊗ a)" by (simp add: a b) finally have "h (a ⊗ b) = h (b ⊗ a)" . thus "a ⊗ b = b ⊗ a" using assms a b unfolding inj_on_def by simp assume ab: "a ⊗ b = 𝟬" hence "h (a ⊗ b) = 𝟬⇘S⇙" by simp hence "(h a) ⊗⇘S⇙ (h b) = 𝟬⇘S⇙" using a b by simp hence "h a = 𝟬⇘S⇙ ∨ h b = 𝟬⇘S⇙" using a b domain.integral[OF A] by simp thus "a = 𝟬 ∨ b = 𝟬" using a b assms unfolding inj_on_def by force qed qed end